The atheroprotective effects of Vitamin E in hypercholestrolemic male rabbits. (November 2020) - Alsahlawi, Zaid M; Ridha, Mahdi M; Hadi, Najah R
Abstract: Background: Atherosclerosis remain as a major health problem occasioning early death in much of the world's people. The ancestry of this diseases related to genetic influences and dietary improperly. The main sources of dietary cholesterol are eggs, meat, and milk products, which induced hypercholesterolemia and atherosclerosis in some species of animals. Materials and Methods: Eighteen local domestic male rabbits will be randomly allocated into 3 groups, 6 in each Group: Group I (n = 6), control; Group II (n = 6), rabbits were receiving 1% cholesterol diet (induced untreated group); Group III (n = 6), 1% cholesterol-diet + Vitamin E (400 mg/kg daily orally). After zero time, four weeks and eight weeks of the study Blood samples were collected for lipid profile (triglycerides, total cholesterol, high density lip protein and serum IL-6, serum high sensitive C-Reactive Protein hs-CRP, serum MCP-1 and serum HMG-box1. Results: Data of this present study has shown that, high fat diet diet caused an increase in serum level of, TG, LDL-C, VLDL-C and TG were increased and decrease serum level of HDL-C compared with the control group in the rabbits feed hyper cholesterolemic diet (P < 0.05). Histologically all induced-untreated rabbit showed increase aortic intima-media thickness (P < 0.05). Vitamin E treated cause significant change on lipid profile (P < 0.05) compared with the induced untreated group. in compared with induced untreated group (P < 0.05), Vitamin E showed significant the change in hs-CRP, IL-6, MCP-1 and HMG-box1.